2009
DOI: 10.1002/jnr.22099
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor‐I‐stimulated Akt phosphorylation and oligodendrocyte progenitor cell survival require cholesterol‐enriched membranes

Abstract: Previously we showed that insulin-like growth factor-I (IGF-I) promotes sustained phosphorylation of Akt in oligodendrocyte progenitor cells (OPCs) and that Akt phosphorylation is required for survival of these cells. The direct mechanisms, however, by which IGF-I promotes Akt phosphorylation are currently undefined. Recently, cholesterol-enriched membranes (CEMs) have been implicated in regulation of growth factor-mediated activation of the PI3K/Akt pathway and survival of mature oligodendrocytes; however, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…However, selective IGF-I stimulation of the IGF-1R in vitro under conditions where insulin levels are sufficient only to stimulate the insulin receptor but not the IGF-IR revealed roles for IGF signalling per se in OPC proliferation and protein synthesis as well as survival (Jiang et al, 2001; Ness et al, 2002; Ness and Wood, 2002; Frederick and Wood, 2004; Cui and Almazan, 2007; Frederick et al, 2007; Romanelli et al, 2007, 2009; Bibollet-Bahena and Almazan, 2009; Min et al, 2012). The effect of IGF-I in multiple processes during development of this lineage has made it difficult to determine whether IGF-I also directly regulates oligodendrocyte differentiation.…”
Section: Mtor In Oligodendrocyte Differentiation and Cns/pns Myelinationmentioning
confidence: 99%
“…However, selective IGF-I stimulation of the IGF-1R in vitro under conditions where insulin levels are sufficient only to stimulate the insulin receptor but not the IGF-IR revealed roles for IGF signalling per se in OPC proliferation and protein synthesis as well as survival (Jiang et al, 2001; Ness et al, 2002; Ness and Wood, 2002; Frederick and Wood, 2004; Cui and Almazan, 2007; Frederick et al, 2007; Romanelli et al, 2007, 2009; Bibollet-Bahena and Almazan, 2009; Min et al, 2012). The effect of IGF-I in multiple processes during development of this lineage has made it difficult to determine whether IGF-I also directly regulates oligodendrocyte differentiation.…”
Section: Mtor In Oligodendrocyte Differentiation and Cns/pns Myelinationmentioning
confidence: 99%
“…IGF-1 is known to activate PI3K and its downstream target Akt, a serine threonine kinase, also known as protein kinase [1012]. IGF-1 binding to its receptor with downstream activation of PI3K and Akt has been demonstrated [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…LY294002, as a synthetic compound [Walker et al, 2000], has been used widely as pharmaceutical tools for the involvement of the PI3K pathway in various biological systems [Romanelli et al, 2009; Tang et al, 2009]. For example, LY294002 has been shown to inhibit rat NPC proliferation [Hsu et al, 2005; Hu et al, 2010], which suggested that PI3K/AKT signal has been implicated in cell cycle control.…”
Section: Discussionmentioning
confidence: 99%